Complete invagination of the vermiform appendix of the cecum – a rare case in surgical practice - B. V. Sigua; V. P. Zemlyanoy; A. A. Kurkov; D. G. Berest; S. A. Vinnichuk; N. G. Lyubimov (Вестник хирургии имени И.И. Грекова)
An extremely rare case of complete invagination of the vermiform appendix in a 45-year-old female patient caused by endometriosis is presented. Difficulties of preoperative diagnostics and determination of treatment tactics in the absence of specific clinical and instrumental data are demonstrated.